Platelet Count Does Not Predict Bleeding in Cirrhotic Patients: Results from the PRO‐LIVER Study. (March 2018) - Basili, S; Raparelli, V; Napoleone, L; Talerico, G; Corazza, G R; Perticone, F; Sacerdoti, D; Andriulli, A; Licata, A; Pietrangelo, A; Picardi, A; Raimondo, G; et al.
Abstract : OBJECTIVES: Thrombocytopenia is a hallmark for patients with cirrhosis and it is perceived as a risk factor for bleeding events. However, the relationship between platelet count and bleeding is still unclear. METHODS: We investigated the relationship between platelet count and major or clinical relevant nonmajor bleedings during a follow‐up of ∼4 years. RESULTS: A total of 280 cirrhotic patients with different degrees of liver disease (67% males; age 64±37 years; 47% Child–Pugh B and C) were followed up for a median of 1, 129 (interquartile range: 800–1, 498) days yielding 953.12 patient‐year of observation. The annual rate of any significant bleeding was 5.45%/year (3.57%/year and 1.89%/year for major and minor bleeding, respectively). Fifty‐two (18.6%) patients experienced a major ( n =34) or minor ( n =18) bleeding event, predominantly from gastrointestinal origin. Platelet counts progressively decreased with the worsening of liver disease and were similar in patients with or without major or minor bleeding: a platelet count ≤50 × 10 3 /μl was detected in 3 (6%) patients with and in 20 (9%) patients without any bleeding event. Conversely, prothrombin time‐international normalized ratio was slightly higher in patients with overall or major bleeding. On Cox proportional hazard analysis, only a previous gastrointestinal bleeding (hazard ratio (HR): 1.96; 95% confidence interval: 1.11–3.47; P =0.020) and encephalopathy (HR: 2.05; 95% confidence interval: 1.16–3.62; P =0.013) independently predicted overall bleeding events. CONCLUSIONS: Platelet count does not predict unprovoked major or minor bleeding in cirrhotic patients.